Development of an AR-Based Learning Media Prototype for Basic Medical Equipment Education Using Assemblr EDU - M Ramadhani (Sah Publisher, 2026)
The rapid advancement of information technology has encouraged the integration of interactive digital media into educational practices, particularly to overcome limitations associated with conventional learning resources. This study aims to develop and evaluate an Augmented Reality (AR)–based learning media prototype for basic medical equipment education using the Assemblr EDU platform. The study addresses challenges such as limited access to physical medical devices, high procurement costs, and safety risks during practical learning by offering an alternative visual and interactive learning solution.This research employed a Research and Development (R&D) approach using a modified Borg and Gall model, consisting of five stages: preliminary study, learning media planning, AR media prototype development, functional testing and evaluation, and prototype refinement. The AR learning media was developed by integrating 3D medical equipment models—including thermometers, stethoscopes, sphygmomanometers, medical masks, and symbolic syringes—along with textual explanations and interactive features. Media feasibility was evaluated through content validation and black box functional testing, focusing on instructional quality, content accuracy, visual appearance, navigation, interaction, and programming functionality. The evaluation results indicate that the developed AR learning media achieved a mean feasibility score of 4.37 for content and instructional aspects and 4.02 for visual and programming aspects, both categorized as Highly Feasible. These findings demonstrate that the media functions effectively and meets the essential criteria for educational use. The AR media supports independent learning, enhances conceptual understanding, and increases user engagement through immersive and interactive visualization. The novelty of this study lies in the development of an accessible AR-based learning media prototype using a low-code platform specifically designed for basic medical equipment education. The results contribute to the application of AR technology in educational media development and provide a foundation for future studies focusing on learning effectiveness, user experience, and broader implementation.